ANALISIS EFEKTIVITAS PROGRAM BULAN SEDEKAH DALAM PENINGKATAN DANA ZIS DI BAZNAS KABUPATEN JEPARA - miswan ansori; Zahrotun Nafisah (Faculty of Sharia and Law Universitas Islam Nahdlatul Ulama, 2022)
This study aims to determine how effective the month of alms program is in increasing the collection of zakat, infaq and alms funds at BAZNAS Jepara Regency, how to collect and distribute zakat, infaq and alms funds at BAZNAS Jepara Regency and what are the supporting and inhibiting factors in the collection and distribution of zakat funds, infaq and alms at BAZNAS Jepara Regency. This research uses field research with observation, interview and documentation techniques. There are two sources of data in this study, namely primary and secondary data sources. The approach used is descriptive qualitative.The results of this study indicate that the effectiveness of the alms month program in increasing the collection of zakat, infaq and alms funds at the national zakat charity agency (BAZNAS) in Jepara Regency has not been effective due to the lack of public awareness to pay ZIS, lack of trust and lack of public understanding of the existing programs in the district. The National Amil Zakat Agency (BAZNAS) of Jepara Regency. The collection of zakat, infaq, and alms funds at the Jepara Regency National Amil Zakat Agency (BAZNAS) has been going quite well. However, in its distribution there are several inhibiting factors, including: a) the validity of the muzakki and mustahiq data b) the lack of human resources at the Jepara Regency National Amil Zakat Agency (BAZNAS) office.